The Clinicopathological Features and Prognoses of Lower Uterine Segment Cancer: A Retrospective, Single-Center Cohort Study - Wang H; Xiao Y; Cai Y; Zhou Y; Chen L; Guo J; Shi X; Liang Z (Dove Medical Press, 2024)
Hao Wang,1 Yinbo Xiao,1 Yumeng Cai,1 Yang Zhou,1 Longyun Chen,1 Jianbin Guo,2 Xiaohua Shi,1 Zhiyong Liang1 1Department of Pathology, Peking Union Medical College Hospital, Chinese Academy of Medical Science & Peking Union Medical College, Beijing, 100730, People's Republic of China; 2Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Chinese Academy of Medical Science & Peking Union Medical College, Beijing, 100730, People's Republic of ChinaCorrespondence: Zhiyong Liang; Xiaohua Shi, Department of Pathology, Peking Union Medical College Hospital, Chinese Academy of Medical Science & Peking Union Medical College, No. 1 Shuaifuyuan, Dongcheng District, Beijing, Tel +86 10-69159353 ; +86 10-69159365, Email liangzy@pumch.cn; shixiaohua3762@foxmail.comIntroduction: This study used single-center data to analyze the clinicopathological features of site-specific endometrial cancer.Methods: Patients with endometrial carcinoma who had undergone surgery at Peking Union Medical College Hospital, China, between March 2016 and January 2022 were enrolled. Clinical information and pathological characteristics were summarized, and microsatellite status was analyzed using the immunohistochemical method. Patient prognoses were measured in terms of the rates of overall survival and progression-free survival.Results: The mean patient age was 49 years (ranging: from 25 to 76 years old), and there was no difference in clinicopathological features between endometrioid and type II endometrial carcinoma in LUSC. The ER and PR expression ratios were 80.4% and 64.3%, respectively, in this LUSC cohort, and the MMR deficiency ratio was 33.9%, including 39.6% in endometrioid carcinoma and 15.4% in type II endometrial carcinoma. Combined MSH2&MSH6 loss was more common than combined MLH1&PMS2 being unexpressed (16.1% vs 12.5%), and dMMR patients differed significantly from the pMMR group in terms of vascular invasion (P=0.003). The combination of chemotherapy and radiotherapy did not provide a statistically significant improvement in prognosis compared to chemotherapy alone.Conclusion: The results of this study showed that LUSC patients tended to be younger and their tumors had less expression of hormone markers. The biological behavior of both endometrioid cancer and type II EC may be similar when EC occurs in this area. Furthermore, this type of tumor also showed a higher incidence of vascular invasion, and the combination of chemotherapy and radiotherapy did not provide significant improvement. Thus, successful treatment of LUSC tumors requires aggressive surgical intervention and a more effective postoperative treatment approach.Keywords: endometrial cancer, lower uterine segment, prognosis